2008
DOI: 10.1002/smll.200800228
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Thin‐Film‐Fracture‐Based Nanowires into Microchip Fabrication

Abstract: One-step device fabrication through the integration of nanowires (NWs) into silicon microchips is still under intensive scientific study as it has proved difficult to obtain a reliable and controllable fabrication technique. So far, the techniques are either costly or suffer from small throughput. Recently, a cost-effective method based on thin-film fracture that can be used as a template for NW fabrication was suggested. Here, a way to integrate NWs between microcontacts is demonstrated. Different geometries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Such Pd-coated rough Si nanowires are depicted in Figure 3 b. [22] The fracture patterns were found to change as a function of stripe width. Notably, such vertical type sensors exhibit a low detection limit of 5 ppm H 2 in air, along with a short response time.…”
Section: Deposition On Prestructured Patternsmentioning
confidence: 98%
“…Such Pd-coated rough Si nanowires are depicted in Figure 3 b. [22] The fracture patterns were found to change as a function of stripe width. Notably, such vertical type sensors exhibit a low detection limit of 5 ppm H 2 in air, along with a short response time.…”
Section: Deposition On Prestructured Patternsmentioning
confidence: 98%
“…The sensing quality originates from grainy structure of the nanowires which changes their electrical conductivity as a result of change in the nanogaps between the grains. The Pd nanowires were fabricated by the fracture approach which can also be used for hydrogen detection [29].…”
Section: Fracture Approachmentioning
confidence: 99%
“…To improve the outcome of the residual deposition and to accelerate the conventional lift-off process, in certain circumstances it is necessary to agitate the sample in an ultrasonic bath filled with a solvent solution. However, such a procedure can lead to the removal not only of the residual material, but also of the fabricated structure, especially when the desired features are very delicate and of nanoscale dimensions [8]. Hence, the lift-off process is often considered to be a trial and error technique, in which optimum process parameters identified with one particular material may not work for another.…”
Section: Introductionmentioning
confidence: 99%